Soldier of the Republic: The Civil War Years of W.H.H. McCall - Ivey, Darren L. (Kansas State University, The Chapman Center for Rural Studies, 2018)
This essay examines the military career of William Henry Harrison McCall, a typical Union officer in the American Civil War. Once the conflict ended, McCall participated in one of the most famous engagements with hostile Indian warriors in American history. The biographical findings are based on genealogical documents, government and archival records, newspaper articles, and numerous survey works on the Civil War's Eastern theater.
Darren L. Ivey , “Soldier of the Republic: The Civil War Years of W.H.H. McCall,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/256.
Keywords: Civil War; Fort Harker; Hays City; Indian Wars; W.H.H. McCall